TINJAUAN YURIDIS TERHADAP PENCURIAN OBAT-OBATAN YANG DILAKUKAN OLEH PEGAWAI RUMAH SAKIT DALAM PERSPEKTIF KUHP (Studi Putusan Pengadilan Negeri Tanjung Balai Nomor 271/Pid.B/2020/PN.Tjb) - Demonstar Hasibuan; Marlina Marlina; Arif Sahlepi (Jurnal Ilmiah METADATA, 2021)
Theft by weight is regulated in Article 363 of the Criminal Code, which consists of two paragraphs, and the first paragraph consists of several sub-paragraphs, namely 1e, 2e, 3e, 4e and 5e. Each of them explains the circumstances and additional criminal elements of the main form of the crime of theft which is regulated in Article 362 of the Criminal Code, which is the basis for criminal aggravation. The investigation carried out by the Tanjung Balai Police Criminal Investigation Unit in uncovering the theft of drugs from the Tengku Mansyur Tanjung Balai Hospital, began with a report from the Tengku Mansyur Tanjung Balai Hospital, namely Zulkifli's brother. The elements of criminal aggravation in the case of drug theft from Tengku Mansyur Tanjung Balai Hospital, namely: carried out by more than two people together by dismantling the window of the medicine warehouse at Tengku Mansyur Tanjung Balai Hospital.